2016
DOI: 10.1089/jmf.2016.3705
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Turmeric Extracts and Curcumin for Alleviating the Symptoms of Joint Arthritis: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Although turmeric and its curcumin-enriched extracts have been used for treating arthritis, no systematic review and meta-analysis of randomized clinical trials (RCTs) have been conducted to evaluate the strength of the research. We systemically evaluated all RCTs of turmeric extracts and curcumin for treating arthritis symptoms to elucidate the efficacy of curcuma for alleviating the symptoms of arthritis. Literature searches were conducted using 12 electronic databases, including PubMed, Embase, Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
210
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(221 citation statements)
references
References 45 publications
3
210
0
8
Order By: Relevance
“…Our results also corroborate the conclusions of two recent reviews which suggested beneficial effects of curcuminoids in the treatment of OA. 48,49 In contrast to those reports, we used SMDs rather than MDs to account for variations in outcome measures across the studies, explored dose-effect relationships, and included one new trial 46 which was not available for those reviews. The heterogeneity observed in the meta-analytic results may have resulted from variation in the reporting quality across the RCTs, differences in the demographic characteristics of study participants, differences in the durations of intervention, and variation in daily dosages and bioavailability of curcuminoids and types of control interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also corroborate the conclusions of two recent reviews which suggested beneficial effects of curcuminoids in the treatment of OA. 48,49 In contrast to those reports, we used SMDs rather than MDs to account for variations in outcome measures across the studies, explored dose-effect relationships, and included one new trial 46 which was not available for those reviews. The heterogeneity observed in the meta-analytic results may have resulted from variation in the reporting quality across the RCTs, differences in the demographic characteristics of study participants, differences in the durations of intervention, and variation in daily dosages and bioavailability of curcuminoids and types of control interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events were not increased with turmeric. 200 Omega-3 fatty acids Omega-3 fatty acids, such as fish oil, are often used by patients as an additive therapy for rheumatoid arthritis. A meta-analysis of 17 studies with a total of 823 patients investigating the role of omega-3 fatty acid supplements in patients with rheumatoid arthritis showed modest benefits of fish oil in reducing pain (SMD −0.26, −0.49 to −0.10), duration of morning stiffness, and the number of tender or swollen joints.…”
Section: Curcumamentioning
confidence: 99%
“…W., Booth, J., 2004;Daily, Yang, & Park, 2016;EMA, 2017;Ghalaut et al, 2012;Gupta et al, 2013;Khajehdehi et al, 2012;Kuptniratsaikul et al, 2014;Kuttan, Sudheeran, & Josph, 1987;Schaffer, Schaffer, & Bar-Sela, 2015). W., Booth, J., 2004;Daily, Yang, & Park, 2016;EMA, 2017;Ghalaut et al, 2012;Gupta et al, 2013;Khajehdehi et al, 2012;Kuptniratsaikul et al, 2014;Kuttan, Sudheeran, & Josph, 1987;Schaffer, Schaffer, & Bar-Sela, 2015).…”
mentioning
confidence: 99%